The Effect of ᵞ -ray doses on Phagocyte Functional activity of Granulocytes by mean of Chemiluminescence - Nazal, Ferial Y. (University of Thi-Qar Journal of Science, 2019)
White blood cells are the fundamental viable defense barrier in the body immune system against foreign bodies such as bacteria parasites viruses. All types of leukocytes have the ability to produce reactive oxygen species such as singlet oxygen 1O2 , super oxide .O2 , hydroxyl radical OH and hydrogen peroxide H2O2 in the process of Phagocytosis and respiratory burst . When leukocytes exhibit respiratory burst, this process will cause light emitting and this will called Chemiluminescence (CL) .The emitted light is very weak and requires some materials to increase the light intensity for detection. Chemiluminescence (CL) is a new technique used in this study to find out the effect of gamma rays on the white blood cells, as used Luminol to increase the detection of light intensity. Gamma ray will produce free radicals from the excitation reactions with the materials. The somatic damage of radiation may be tolerated if whole body exposure was in a low rate and extended over a long period of time. Sensitivity, resistance and reactive activity of White blood cells (WBCs) will react differently to gamma radiation according to their characteristics and body repair mechanisms. Gamma ray doses have been studies to see it is effect on control and test blood cell samples. This was done under same PH. This will make changing in the CL values.